Low-Loss Broadband Parabolic Dielectric Reflector in Silicon-on-Insulator. - Moreno-Pozas, Laureano; Barona-Ruiz, Miguel; Halir, Robert; De-Oliva-Rubio, José; Rivas-Fernández, Jorge; Molina-Fernández, Íñigo; Wanguemert-Pérez, Juan Gonzalo; Ortega-Moñux, Alejandro (My University, 2025)
In this work, we designed a spot-size converter based on parabolic dielectric reflector that couples light from a 0.5 μm-wide waveguide to a 285 μm-wide waveguide, i.e. has an expansion factor of ×570. We assessed its behavior on the silicon-on-insulator commercial platform. We experimentally report inser-tion losses of less than 0.35 dB in an unprecedented bandwidth of more than 380 nm. We also provide a full analytical design method for arbitrary expansion fac-tors, which does not require any simulation.
Keywords: Fotónica; Silicio sobre aislante; Dispositivos dieléctricos; Integrated Photonics; Silicon-on-insulator; Spot-size Converter; Dielectric Reflector